Acute Toxicity Comparison of Single-Walled Carbon Nanotubes in Various Freshwater Organisms. (14th January 2015) - Sohn, Eun Kyung; Chung, Young Shin; Johari, Seyed Ali; Kim, Tae Gyu; Kim, Jin Kwon; Lee, Ji Hyun; Lee, Yong Hwa; Kang, Sung Wook; Yu, Il Je
Abstract : While the commercialization of single-walled carbon nanotubes (SWCNTs) is rapidly expanding, the environmental impact of this nanomaterial is not well understood. Therefore, the present study evaluates the acute aquatic toxicity of SWCNTs towards two freshwater microalgae ( Raphidocelis subcapitata and Chlorella vulgaris ), a microcrustacean ( Daphnia magna ), and a fish ( Oryzias latipes ) based on OECD test guidelines (201, 202, and 203). According to the results, the SWCNTs inhibited the growth of the algae R. subcapitata and C. vulgaris with a median effective concentration (EC50 ) of 29.99 and 30.96 mg/L, respectively, representing "acute category 3" in the Globally Harmonized System (GHS) of classification and labeling of chemicals. Meanwhile, the acute toxicity test using O. latipes and D. magna did not show any mortality/immobilizing effects up to a concentration of 100.00 mg/L SWCNTs, indicating no hazard category in the GHS classification. In conclusion, SWCNTs were found to induce acute ecotoxicity in freshwater microalgae, yet not in D. magna and medaka fish.